PERANCANGAN APLIKASI EVALUASI KINERJA PENELITIAN PERGURUAN TINGGI MENGGUNAKAN METODE NAIVE BAYES - Andrian Andrian (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
This application is distributed to the management of scientific research and publication is an application that can help in the research report are inputting data via intranet and internet. The purpose of making these applications simplify the research process conducted by researchers and can monitor the progress of the research conducted UNTAR lecturer. Applications developed with the classification technique which is one of the techniques of data mining. Classification methods are used for applications that Naive Bayes algorithm. Data to be processed is the data research faculty from 2013-2014. Results of classification are categorized lecturer (presenter or not presenters), (researcher or not researcher), (publication or not publication). The classification results are expected to be used as an ingredient LPPI to monitor faculty research activities. Key wordsData Mining, Performance Evaluation, Research and Scientific Publications, Classification, Naive Bayes Methods,  University Tarumanagara.